- #1

- 8

- 0

f:A-> A = {(1,2),(2,3),(3,1)}

g:A->A = {(1,2),(2,1),(3,3)}

how would we calculate (f O g)?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter aaa59
- Start date

- #1

- 8

- 0

f:A-> A = {(1,2),(2,3),(3,1)}

g:A->A = {(1,2),(2,1),(3,3)}

how would we calculate (f O g)?

- #2

- 352

- 0

For example, g(2) = 1 and f(1) = 2. So h(2) = 2. Hope this helps.

- #3

- 8

- 0

i think i got it.

so: g(1) = 2 and f(2) = 3. therefore h(1)=3. am i right?

so: g(1) = 2 and f(2) = 3. therefore h(1)=3. am i right?

- #4

- 352

- 0

Yes.

- #5

CompuChip

Science Advisor

Homework Helper

- 4,306

- 48

[tex]h = f \circ g[/tex]

as just "shorthand" for the function defined by

[tex]h(x) = f(g(x))[/tex]

Share:

- Replies
- 6

- Views
- 2K